EDUKASI PENCEGAHAN DAN PENANGANAN STUNTING: education on preventing and handling stunting - Susanti, Linros; Ika, Hendrika (Pergizi Pangan DPD NTT, 2024)
Abstract The first thousand days of life (1000 HPK) are very important in human growth and development. About 80% of the development of the brain and body organs occurs during the golden period (1000 HPK). Missing the opportunity to grow optimally during this period can cause stunting with long-lasting impacts. Education for mothers of toddlers includes improving nutrition, monitoring routine growth every month, and monitoring development regularly at least once every 3 months. The activity was carried out with the aim of increasing community knowledge about stunting in Oesusu Village, Kupang Regency in September 2023. Implementation used the